Management and reporting of safety incidents by residential care facilities in Ireland: A thematic analysis of statutory notifications. (25th July 2022) - McGrane, Niall; O'Regan, Stephaine; Dunbar, Paul; Dunnion, Mary; Leistikow, Ian; Keyes, Laura
Abstract: The prevention of safety incidents (SI) in health and social care settings is an ongoing undertaking. Limited research has been conducted on SIs outside of acute care. Internationally residential care facilities (RCFs) are typically regulated to promote quality and safeguarding. A part of this regulation is the statutory responsibility of RCFs to notify the regulator about SIs. Notifications include details surrounding SIs and are used to inform the regulatory monitoring approach. The recent development of the Database of Statutory Notifications from Social Care in Ireland facilitates in‐depth analysis of notifications which can be used to inform the management of SIs and thus, improve quality and safety. The aim of this study was to analyse narratives provided in statutory notifications for older persons and people with disability, in order to identify current management of SIs, system vulnerabilities and reporting practices. A Qualitative Descriptive approach was taken. A random sample of notifications received in 2018 was drawn and stratified by service‐type and notification‐type. Data extraction was conducted against priori agreed target areas of management, system vulnerabilities and reporting practices. Inductive thematic analysis was used identifying two parent themes: 'chronology' and 'regulatory input'. 'Chronology' subthemes included 'pre‐event', 'immediate response' and 'continued response'. Measures that are resident focused and follow policies and protocols in RCFs to prevent or mitigate the seriousness of SIs were evident in the immediate response and continued response. The actions taken in the immediate and continued response in turn became part of the pre‐event of future SIs. Under 'regulatory input' subthemes included 'inaccurate reporting', 'lines of inquiry', 'requests for further information', 'identification of repetitive patterns' and 'satisfactory conclusion'. In conclusion, RCFs manage SIs with short and longer term actions focused on resident wellbeing. These actions in turn become part of the pre‐event of future SIs. Regulatory input highlighted regulatory burden.